Family and child with central nervous system lesion - Polovina Prološčić, Tajana; Vidović, Vesna, liječnica; Polovina, Svetislav, liječnik; Polovina, Andrea (2009)
Abstract: The aim of the study was to assess if mothers of children with severe forms of cerebral motor impairment perceive their family strength differently than mothers of children with moderate forms of this disorder, as compared.The study included 135 children with cerebral motor impairment. Children were divided into two groups according to the clinical picture severity and their development was followed-up over a one-year period The course of rehabilitation was assessed by the method of locomotor system functional evaluation.After 12-month rehabilitation, the method of targeted structured interview with the mothers was used. The mothers filled out a questionnaire on family strength, which consisted of 12 questions on their perception of family strength. The present study confirmed the need and efficacy of rehabilitation treatment in children with motor development abnormalities. Study results showed no significant differences in the values obtained by the family strength questionnaire, indicating that there was no statistically significant difference between the two groups in their coping with stressors. It is postulated that the family crisis induced by the birth of a child with risk symptoms must have brought the parents closer and reinforced the family as a whole, irrespective of the severity of the child’s clinical picture
Bibliografija: 21 jed
Sažetak
Keywords: Oštećenje središnjeg živčanog sustava -- Djeca -- Obitelj